A Review of the Role of Intangible Axis toward the Pathok Negoro’s Design Concept, Yogyakarta - Silvia Meliana; Octaviana Sylvia Caroline (Humaniora, 2020)
The research aimed to review the role of the ‘mystical’ imaginary axis in Javanese cosmology in the Yogyakarta that might affect the inner spaces of the Pathok Negoro mosques (Ploso Kuning, Babadan, Dongkelan, and Mlangi). The research question was how Yogyakarta’s imaginary axis affected the inner spaces of these four Pathok Negoro. Yogyakarta was known to have a unique Javanese cosmology, cultural, and social life character compared to several cities on the island of Java. Yogyakarta kept a harmonious power between human life and the universe and still hold strong Javanese animism and was still tightly coupled with the city’s modern life. Human harmony with the universe was seen in the axis of a city that consisted of two main axes in the direction of the compass, namely north to south and east to west. The research applied a qualitative method by doing a literature study and observation. The research shows that the imaginary axis plays an essential role in Yogyakarta’s urban design and creates a sustainable concept of the four Pathok Negoro. However, it is not directly involved in the order of the inner space of the architecture design of each mosque.